STRATEGI KOMUNIKASI DINAS KEBUDAYAAN DAN PARIWISATA DALAM UPAYA PENGEMBANGAN OBJEK WISATA BUDAYA RUMAH BENTANG MELAPI I DI DESA MELAPI KECAMATAN PUTUSSIBAU SELATAN KABUPATEN KAPUAS HULU - Dana Oktavian E.01108044 (FISIP Universitas Tanjungpura, 2013)
This thesis is given detail and deeper information about Long House of Taman Kapuas Melapi I Sub Ethnic Group as cultural tourism object with case study about communication strategy of Culture and Tourism Department of Kapuas Hulu Regency. The writer hopes this thesis will give better suggestion to make communication strategy of culture and tourism of Kapuas Hulu Regency to be more effective and efficient.Based on research finding, communicative strategy of Cultural and Tourism Department of Kapuas Hulu Regency is good enough. But, it needs more maximal effort to make good cooperation with every society elements and also to explore the use of media that they had. It means that every Kapuas Hulu tourism potential and Long House of Taman Kapuas Melapi I will widely known, and can attract many visitors and get people special attention. Key words: communication strategy, cultural tourism, Long House tourism, and media effectiveness.